(untitled) (Research, Society and Development, 2021)
This article aims to analyze the feasibility of water reuse in the use of air conditioners used at Christus Faculdade do Piauí, CHRISFAPI, in Piripiri-PI, as a set of actual case studies, based on data collections made in the dripping of the drains of the apparatus of the aforementioned faculty. With reuse, impacts resulting from inappropriate disposal of water will be visibly commuted. The air conditioners have particularities according to the brand, among them: temperature, energy consumption and Btus (British Thermalunits Thermal Unit). 99 ceiling floor type air conditioners have been listed, with a capacity of 2200 Btus, of two distinct brands, Carrier e Spring, installed in 43 classrooms. For the collection of discarded water, two basins were used, one for each type in an interval of one hour. After collection, with the aid of a beaker, the exact volume of water wasted during the period mentioned above has been measured, and reproduced to the remaining machines, reaching a total of 718.36 liters of water per school day. The results obtained show a viable alternative for the storage and reuse of water that would be wasted. Therefore, this article brought to the institution not only information on the quantity of water that can be reused in the Faculty itself, but only the benefits to come for other purposes within the institution.